1982
DOI: 10.1093/jn/112.7.1320
|View full text |Cite
|
Sign up to set email alerts
|

Epiphyseal Plate Development in the Zinc-Deficient Rat

Abstract: The effect of zinc deficiency on shearing strength, histological changes and proline utilization of the epiphyseal plate of the tibia of the weanling male rat was studied. A diet was fed based on sprayed egg white and containing less than 2 mg of zinc per kilogram. Over 27 day, the force required to displace the epiphysis of the zinc-deficient (ZD) rats was always less than that required for pair-fed (PF) controls. After 18 days, approximately 15% more force was required to displace the epiphysis of the PF rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…When pair-feeding was used, the effects of Zn deficiency on bone were attributed to reduced osteoblast modeling activity only [3,38] or in combination with reduced osteoclast numbers [7]. In the present study, stepwise increases in dietary Zn produced incremental differences in metaphyseal trabecularization, consistent with previous comparisons between severely deficient and adequate groups [1,[4][5][6][7]. Here, graded levels of dietary Zn ranged from severely deficient (2.5 μg/g) to adequate (30 μg/g), and normal growth was maintained by 7.5 μg Zn/g diet.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…When pair-feeding was used, the effects of Zn deficiency on bone were attributed to reduced osteoblast modeling activity only [3,38] or in combination with reduced osteoclast numbers [7]. In the present study, stepwise increases in dietary Zn produced incremental differences in metaphyseal trabecularization, consistent with previous comparisons between severely deficient and adequate groups [1,[4][5][6][7]. Here, graded levels of dietary Zn ranged from severely deficient (2.5 μg/g) to adequate (30 μg/g), and normal growth was maintained by 7.5 μg Zn/g diet.…”
Section: Discussionsupporting
confidence: 87%
“…Later, O'Dell et al [2] (1957) also reported defective hypertrophic chondrocyte proliferation related to low dietary Zn, providing additional evidence for an osteogenic Zn requirement. Bone formation in Zn-deficient animals is characterized by retarded growth plate activity [3][4][5][6] and is associated with reduced cancellous and trabecular volume [3,7,8]. The biophysical consequences of these events include decreased longitudinal and radial expansion of long bones, with increased susceptibility to breakage due to applied physical stress [3,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Zn deficiency weakens protein synthesis (Giugiano & Millward, 1987), making Zn an essential factor for the synthesis of proteins (Hendy et al, 2001). Also, Zn is known to be necessary for normal collagen synthesis and mineralization of bone that has been demonstrated to be essential for normal growth of both human and animal skeletal systems (Bougle et al, 2004; Doherty et al, 2002; Eberle et al, 1999; Elmstachl et al, 1998; Hosea et al, 2004; Hyun et al, 2004; Ovesen et al, 2001; Peretz et al, 2001; Rossi et al, 2001; Seco et al, 1998; Suwarnasarn et al, 1982;). It therefore has been considered that Zn can be a critical factor to affect skeletal development and bone formation.…”
Section: Introductionmentioning
confidence: 99%
“…Zinc (Zn) is a dietary essential trace mineral known to be necessary for normal collagen synthesis and mineralization of bone [1,2]. Zn has been demonstrated to be essential for normal growth of both human and animal skeletal systems [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%